FORMATION OF SOCIOLINGUISTIC COMPETENCE OF STUDENTS STUDYING GERMAN LANGUAGE: FACTORS AND CONDITIONS - Ziyaeva, Sevara (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The presented work deals with the process of teaching the sociolinguistic competence of students specializing in the field of German philology. Specific criteria and indicators that allow assessing the level of students' achievements in the field of sociolinguistic competence within the framework of this study have been formulated. The relevance of the work is due to the growing importance of sociolinguistic competence in the modern world, especially in the context of intercultural communication and globalization. Students studying foreign languages, in particular German, need to acquire sociolinguistic knowledge and skills for successful interaction in a multilingual and multicultural society. To achieve the objectives of the study, a variety of methods were used, including the analysis of scientific literature, interviewing students, observing their communication practices and analyzing written works. Specific indicators and criteria for assessing their sociolinguistic competence were identified and specified, such as the ability to adapt to the linguistic and cultural characteristics of native speakers, understanding of sociolinguistic differences, the ability to apply sociolinguistic knowledge in real situations of communication. As a result of the study, it was found that the training of sociolinguistic competence depends on various factors and conditions, including the level of motivation, the educational environment, the availability and quality of educational materials and methods. Weaknesses and problems in the formation of sociolinguistic competence have been identified. The recommendations have been proposed for optimizing the educational process.
Keywords: competence; sociolinguistic competence; speech behavior; social relations; competence formation; criteria for determining the level of competence development